2006
DOI: 10.1111/j.1432-2277.2006.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

The calcineurin activity profiles of cyclosporin and tacrolimus are different in stable renal transplant patients

Abstract: Summary Cyclosporin and tacrolimus remain the cornerstone immunosuppressive drugs in organ transplantation. Dosing and monitoring these drugs is based on pharmacokinetic protocols, but measuring a pharmacodynamic parameter, calcineurin phosphatase (CaN) activity, could be a valuable supplement in determining optimal doses. Forty stable renal transplant patients were investigated three times in a 6‐month period. Blood samples were drawn at 0, 1, 2, 3 and 4 h after oral intake of tacrolimus (FK) or cyclosporin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…2,7,13,34 As previously described by other authors, our results showed that Tac-IR-treated patients reached significant reduction of CNA in the first hours after drug intake (1-3 hours) and a recovery to baseline levels after 4 hours. 17,[35][36][37] This rapid recovery could be clinically relevant, especially in nonadherent recipients in which the evening drug intake was delayed. In this context, a prolonged under-immunosuppression during that interval could promote the activation of alloreactive T-cells and, ultimately, contribute partly to graft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…2,7,13,34 As previously described by other authors, our results showed that Tac-IR-treated patients reached significant reduction of CNA in the first hours after drug intake (1-3 hours) and a recovery to baseline levels after 4 hours. 17,[35][36][37] This rapid recovery could be clinically relevant, especially in nonadherent recipients in which the evening drug intake was delayed. In this context, a prolonged under-immunosuppression during that interval could promote the activation of alloreactive T-cells and, ultimately, contribute partly to graft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…[25] found a greater calcineurin inhibition of cyclosporine than of tacrolimus using phosphorylated peptides and liquid scintillation. In his study including patients with well‐functioning grafts, a minimal calcineurin phosphatase activity in tacrolimus‐treated patients was sufficient to maintain a stable graft function [25]. To see if these significantly different calcineurin activity profiles have an impact on graft function, we monitored inulin and PAH clearances of a subgroup of groups A and B for 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the transient PD profile observed after morning Tac dose characterized by a rapid return to pre-dose levels once the I nadir was reached, which differs to the more sustained inhibition after the I nadir , which was noticed following night dose. Previous studies also showed this rapid recovery of CN activity to pre-dose levels after the morning Tac dose (Koefoednielsen and Gesualdo, 2002;Koefoed-Nielsen et al, 2006;Iwasaki et al, 2018;Fontova et al, 2021). Other studies investigating lymphocyte activation have shown circadian rhythms displaying higher proinflammatory cytokine secretion during night time (Benedict et al, 2007;Fortier et al, 2011).…”
Section: Discussionmentioning
confidence: 53%